Impact of staffing levels and resources of intensive care units on compliance to standard mechanical ventilator guidelines: A city‐wide study in times of COVID‐19 pandemic. Issue 2 (1st April 2022) - Rashid, Khalid; Ansar, Farrukh; Khan, Yahya; Rashad, Nabhan; Rehman, Hafeez; Shah, Syed Zarak; Ullah, Shahid; Waheed, Muhammad
Abstract: Background: The COVID‐19 pandemic has affected millions and resulted in a considerable strain on healthcare systems around the world. Intensive care units (ICUs) are reported to be affected the most because significant percentage of ICU patients requires respiratory support through mechanical ventilation (MV). Aim: This study aims to examine the staffing levels and compliance with a ventilator care bundle in a single city in Pakistan. Methods: A cross‐sectional survey of 14 ICUs including medical and surgical ICUs was conducted through a self‐structured questionnaire including a standardized ventilator care bundle. We assessed the compliance of ICU staff to ventilator care bundle and calculated the correlation between staffing patterns with compliance to this bundle. Results: The unit response rate was 64% (7/11 hospitals). Across these seven hospitals, there were 14 functional ICUs (7 surgical and 7 medical). The Mean (SD) numbers of beds and ventilators were 8.14 (3.39) and 5.78 (3.68) while the average patient‐to‐nurse and patient‐to‐doctor ratio was 3: 1 and 5:1 respectively. The median ventilator care bundle compliance score was 26 (IQR = 21–28) out of 30, while in medical and surgical ICUs, median scores were 24 (IQR = 19–26) and 28 (IQR = 23–30) respectively. The perceived least compliant component was head elevation in ventilated patients. Correlation analysis revealed that 24 h a day, 7 days a week onsite cover of Advanced Cardiovascular Life Support certified staff was positively correlated with the ventilator care bundle score ( r s = 0.654, p value = .011). Similarly, 24‐h cover of senior ICU nurses was significantly correlated with the application of chlorhexidine oral care ( r s = 0.676, p value = .008) while routine subglottic aspiration was correlated with the number of doctors ( r s = 0.636, p value = .014). Conclusion: Our study suggests that ICUs in Peshawar are not well staffed in comparison with international standards and the compliance of ICUs with the ventilator care bundle is suboptimal. We found only a few aspects of ventilator care bundle compliance were related to nursing and medical staffing levels. Relevance to clinical practice: Critical care staffs at most of the medical ICUs in Peshawar are not compliant with the standard guidelines for patients on mechanical ventilation. Moreover, the staffing levels at these ICUs are not in accordance with international standards. However, this study suggests that staffing levels may not be the only cause of non‐compliance with standard mechanical ventilator guidelines. There is an urgent need to design and implement a program that can enhance and monitor the quality of nursing care provided to mechanically ventilated patients. Lastly, nurse staffing of ICUs in Pakistan must be increased to enable high quality care and more doctors should be trained in critical care.